Optimization of Cellulase Production by Chaetomium Globosum Strain 414 Using Oil Palm Empty Fruit Bunch Fibre as Substrate - Md. Shah, Umi Kalsom (1997)
The production of three major components of cellulase (FPase, CMCase and 13-glucosidase) by Chaetomium globoslim strain 414 was studied in a shake flask experiment. The effects of physical and chemical treatments on the oil palm empty fruit bunch (OPEFB) fibre for subsequent use as substrate for cellulase production were investigated. The effects of different types and concentrations of nitrogen sources on cellulase production were also examined. The optimized medium composition obtained from the shake flask experiment was used for cellulase production in a 2L stirred tank ferrnenter (impeller tip speed = 1.64 mls) where the effect of different levels of dissolved oxygen tension (DOT) at a fixed agitation speed on cellulase production was investigated. The experimental data obtained from batch fermentations in a shake flask and the fermenter using the optimized medium were analysed to form the basis for a kinetic model ofthe process. The partially purified cellulase preparation from this fungus was used for the saccharification of OPEFB fibre. The effect of different methods of treatment of OPEFB fibre on the rate and degree of hydrolysis was investigated.The use of2-mm OPEFB fibre increased cellulase production about two fold compared to 10-mm fibre. Chemical treatment significantly increased the cellulose and reduced the lignin contents. Cellulase activities, obtained from fermentation using OPEFB fibre treated with 0.5% RN03 followed by autoclaving were about three times higher than those obtained in fermentation using pure celluloses. The cellulase of C. globosum strain 414 contained a high proportion of l3-glucosidase with the ratio of specific activity of l3-glucosidase to FPase of about 8. Peptone gave the highest cellulase production followed by yeast extract, urea, KN03 and (NH4)2S04' A good agreement between the calculated data and the experimental data for both cell growth and cellulase production were observed, suggesting that the proposed model based on logistic and Luedeking-Piret equations is sufficient to describe the growth of C. globosum strain 414 and cellulase production. The maximum activities of FPase, CMCase and l3-glucosidase obtained from fermentation with 50% DOT were 2.5, 59.5 and 12.8 U/m), and these gave the overall productivities of20.8, 495 and 53.3 U/L.h, respectively. Cellulase production in stirred tank fermenter were significantly higher than that obtained in shake flask. The yield and overall productivity of the saccharification of the autoclaved OPEFB fibre treated with 2% NaOH were 0.7600 g reducing sugar/g OPEFB and 0.0178 g reducing sugar/g cellulose.h, respectively.